The withdrawal of the state from economic activity: An Austrian capital market perspective - Christian Helmenstein (Institute for Advanced Studies (IHS), 1995)
In this paper we investigate the success of recent privatization in Austria from a capital market perspective. The empirical analysis draws upon the concept of initial public offerings indexes to document the medium-run aftermarket performance of initial public offerings (IPOs). Due to certain peculiarities, governmental IPOs outperform non-governmental IPOs in terms of cumulative average returns. Among the approaches discussed, the theory of property rights, together with the economic theory of politics, appears to be particularly appealing in explaining this phenomenon. If market participants adjust their investment decisions accordingly, the superior performance of governmental IPOs must, however, be expected to vanish during later stages of a privatization program. The withdrawal of the state from the ownership of enterprises has repercussions on the expansion of existing private companies due to rising capital costs. Privatization programs thus temporarily inhibit the substitution of inside equity by outside equity in private companies. – – Diese Arbeit untersucht den Erfolg der jüngsten Privatisierungen in Österreich aus der Perspektive des Kapitalmarktes. Um die mittelfristige Performanz von Neuemissionen auf dem Wiener Sekundärmarkt zu dokumentieren, werden verschiedene Erstemissionsindexes (IPOX) konstruiert. Wir zeigen, daß sich Erstemissionen mit öffentlichen Voreigentümer im Vergleich zu solchen mit privatem Voreigentümer überdurchschnittlich gut entwickeln. Unter den Ansätzen, die zur Erklärung dieses Phänomens diskutiert werden, erweist sich besonders die Theorie der Eigentumsrechte sowie die Ökonomische Theorie der Politik als schlüssig. Da zu erwarten ist, daß die Marktteilnehmer ihr Investitionsverhalten den aufgezeigten Möglichkeiten zur Erzielung einer überdurchschnittlichen Rendite anpassen werden, ist während späterer Phasen eines Privatisierungsprogrammes mit einem Abbau der Überperformanz staatlicher Neuemissionen zu rechnen. Der Rückzug des Staates aus der Wahrnehmung ökonomischer Aktivitäten hat daneben Rückwirkungen auf die Expansionsmöglichkeiten privater Unternehmungen. Aufgrund steigender Kapitalkosten gewinnt zumindest temporär die Innenfinanzierung gegenüber der Außenfinanzierung an Attraktivität.
Keywords: C33; G12; C43; G14; 330; initial public offerings; privatization; stock market index; performance analysis; Privatisierung; Emissionsgeschäft; Aktienindex; Österreich